2004
DOI: 10.1074/jbc.m409435200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Anaerobic Dehalorespiration by the Transcriptional Activator CprK

Abstract: Desulfomonile, Desulfitobacterium, and Dehalobacter are anaerobic microbes that can derive energy from the reductive dehalogenation of chlorinated organic compounds, many of which are environmental pollutants. There is very little information about how anaerobic dehalorespiration is regulated. An open reading frame within the Desulfitobacterium dehalogenans chlorophenol reductase (cpr) gene cluster (cprK) was proposed to be a transcriptional regulatory protein (Smidt, H., van Leest, M., van der Oost, J., and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
47
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 38 publications
5
47
1
Order By: Relevance
“…Most of rdh gene clusters are also associated with one rdhK subunit in various orientations. The rdhK-encoded proteins clearly belong to the large family of CRP/Fnr regulatory proteins from which CprK members of Desulfitobacterium dehalogenans and Desulfitobacterium hafniense DCB-2 were extensively studied and represent the paradigmatic DNA-binding regulatory protein for the respective chlorophenol reductive dehalogenase (cpr) operons [48][49][50][51][52][53][54][55][56] figure 3). First, a strong correlation could be established between the level of sequence identity (see also electronic supplementary material, table S7) and the genetic organization of the predicted rdh operons.…”
Section: (I) Multiple Reductive Dehalogenase Homologue Gene Clusters mentioning
confidence: 99%
“…Most of rdh gene clusters are also associated with one rdhK subunit in various orientations. The rdhK-encoded proteins clearly belong to the large family of CRP/Fnr regulatory proteins from which CprK members of Desulfitobacterium dehalogenans and Desulfitobacterium hafniense DCB-2 were extensively studied and represent the paradigmatic DNA-binding regulatory protein for the respective chlorophenol reductive dehalogenase (cpr) operons [48][49][50][51][52][53][54][55][56] figure 3). First, a strong correlation could be established between the level of sequence identity (see also electronic supplementary material, table S7) and the genetic organization of the predicted rdh operons.…”
Section: (I) Multiple Reductive Dehalogenase Homologue Gene Clusters mentioning
confidence: 99%
“…Upon binding of CHPA, CprK activates transcription of dehalobox-containing promoters in D. dehalogenans (11,12). DNA binding studies have shown that CprK1 and CprK are only capable of binding its target DNA when the protein is in its reduced state (10,12). Recently, the x-ray structures of oxidized CprK1 from D. hafniense in complex with CHPA and reduced CprK from D. dehalogenans in its unliganded form have been determined by Joyce et al (13).…”
mentioning
confidence: 99%
“…Previously, a close homologue called CprK was identified in the related halorespiring bacterium, D. dehalogenans, which shows 91% sequence identity with CprK1 from D. hafniense. Upon binding of CHPA, CprK activates transcription of dehalobox-containing promoters in D. dehalogenans (11,12). DNA binding studies have shown that CprK1 and CprK are only capable of binding its target DNA when the protein is in its reduced state (10,12).…”
mentioning
confidence: 99%
“…When the cultures were grown with alternative electron acceptors, such as fumarate or nitrate, CprA transcription ceased within the first subcultivation and was induced within less than 30 min (21). A CRP/FNR-like transcriptional activator, CprK, encoded within the cpr operon, was shown to interact with the DNA upstream of the cpr promoter region only when Cl-OHPA was bound to the protein (18). A direct role of CprK in the induction of dehalogenase gene expression in D. dehalogenans was assumed, and a model for transcriptional regulation of cprA expression was developed (13).…”
mentioning
confidence: 99%